A Simple Approach to Recognize Axial Direction of ReS2 Single Crystals Grown by Chemical Vapor Deposition. Issue 8 (28th June 2018) - Chen, Peng; Wang, Jianyu; Lu, Yan; Zhang, Sihong; Wang, Zhendong; Wang, Li
Abstract : It is important to recognize the axial direction of ReS2 single crystals, with considerable anisotropy in electrical and optical properties, which are expected to have a wide application in photoelectric devices. Here, we successfully synthesize ReS2 single crystals with triangle and parallelogram shapes on SiO2 substrate by a chemical vapor deposition (CVD) method and propose a simple approach to recognize the axial direction of ReS2 single crystals just by comparing the ratio of the edge lengths, which are confirmed by transmission electron microscopy images. In addition, the mobility of a prepared ReS2 field effect transistor is 8.16 cm 2  V −1  s −1 and the on/off ratio is up to 10 5 . Abstract : ReS2 single crystals with triangle and parallelogram shapes are successfully grown on SiO2 substrate by a chemical vapor deposition method. Importantly, Chen et al. propose a simple approach to recognize axial direction of ReS2 single crystals just by comparing the ratio of the edge lengths, which provides a great convenience for identifying the axis direction without complex procedures and causing any damage.